Differences in playing reversal balls on matches of the finalists on the football World Championship 2010 - Dosic, N. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
The reversal ball is one of technical and tactical element which is performed in the attack phase of football game in all three zones of the field. The work represents an attempt of deeper understanding the structure of competitive activity in football game, what can have practical value in efficient programming in the preparation of football players. In the work are evidenced frequency of playing reversal balls per 7 games ( total of 14 ) played by the Representation of Spain and the Netherlands on this Championship. Here were represented the results related to playing of reversal balls with one touch i.e. "playing from the first". In the processing of the data collected is applied the statistical software SPSS 15. For comparison of the evidenced frequencies received by observation of the matches of the two Representations recorded on DVD is applied the nonparametric Man Witni U test technique. On 14 observed games were in total observed 693 played reversal balls with one touch. Of this number the Representation of Spain played 398, and the Representation of the Netherlands 295. From six observed variables statistically significant differences were observed by two variables. And that when were played reversal balls with one touch to the same player from which the ball is received , and that in the zone of attack organization. Z value is - 1.994, and the significance level 0,046. The second variable by which is determined statistically significant difference is by playing of reversal balls with one touch to the same player from which the ball is received and that in the zone of final attack.